Estación calle 72 : centro comercial, empresarial y de transporte (2017)
"The project located on the western side of Caracas Avenue with Calle 72 (locality of Barrios Unidos), responds to an urban intervention that has as a reference point the elevated metro system. Therefore, the Station Calle 72 looks to be an iconic project as it is the final stop of the first stage of the metro line. This reinterprets the way we relate to the city of Bogota and its habitants. Furthermore, taking mobility as an aspect to be enhanced, the station proposes to activate human interaction through spaces that promote permanence as well as complementary activities such as commerce and an office tower. Also, the project is connected to a transportation hub which complements the convergence of the different forms of transportation in this point of the city".-- Tomado del Formato de Documento de Grado.